REVISITING LEARNING OUTCOME STATEMENTS IN TESOL SUBJECT - Wahyuni, Sri (Jurnal Penelitian Pendidikan, 2019)
There has been a shift in paradigm in education from traditional/teacher-centered approach into student-centered/outcome approach internationally. It is, therefore, undeniable that it affects the development of higher education curriculum in Indonesia in which it is mandated that it should be developed under the National Qualification Framework-KKNI. It, consequently, requires the formulation of learning outcomes focusing on what students should be able to do and demonstrate upon completing learning experiences. The present study intends to describe how learning outcomes of Theories and Principles in TESOL subject are formulated. Moreover, it examines the linking among the existing learning outcomes, teaching and learning activities and assessment. This analytical descriptive qualitative study employs document review method to analyze data. In addition, the analysis adopts the guidelines of writing learning outcomes by Kennedy et al (2005) and learning outcomes evaluation form by Popenici Millar (2015). The results show that the existing learning outcomes developed are in the cognitive (knowledge aspect) and psychomotor (skill aspect) domain. However, the learning outcomes in the affective domain are not yet completely developed. The existing learning outcomes have been aligned to the study program outcomes and used action verbs indicating development of learning activities. Besides, there has been good alignment of the learning outcomes and teaching learning activities. However, linking of the outcomes, teaching learning activities, and the assessment needs to be more developed.